METHODS TO IMPROVE THERMAL STABILITY OF CONCRETE BASED ON MINERAL AND CHEMICAL ADMIXTURES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper presents methods for improving the thermal stability of concrete used in high-temperature environments such as road pavements, industrial furnaces, power plants, and solar energy facilities. The scientific novelty lies in the combined use of mineral admixtures (metakaolin, microsilica, slag) and chemical admixtures (polycarboxylate-based superplasticizer and hydrophobic agent) and in the comprehensive analysis of their effects on the microstructure of concrete. Concrete mixes were prepared using PC 400 D0 and PC 500 D0 cements and cured for 28 days before being subjected to thermal exposure between 100°C and 800°C. Compressive strength, elasticity modulus, mass loss, water absorption, and microstructural analyses were performed. Results showed that the combination of 20% metakaolin, 0.8% superplasticizer, and 0.5% hydrophobic additive maintained 80–85% of compressive strength up to 600°C. Even at 800°C, strength reduction was limited to 15–20% compared to ordinary concrete. The hydrophobic agent reduced internal vapor pressure and prevented cracking, while microsilica enhanced C–S–H phase formation and decreased microporosity. The findings are applicable to developing thermally stable concretes suitable for Uzbekistan’s climate and local raw materials.